THE EFFECT OF ENVIRONMENTAL PERFORMANCE ON ECONOMIC ERFORMANCE WITH ENVIRONMENTAL DISCLOSURE AS INTERVENING VARIABLE (SURVEY ON MANUFACTURING COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2019 2020 PERIOD) - Ali, Muhammad; Dewi, Shafira Annasya; Srimorinto, Renatha; Fajrina, Desti Alda; Rahayu, Anggita Muthia; , Topan (CENTRAL ASIA AND THE CAUCASUS, 2022)
The purpose of this research was to determine the effect of Environmental Performance on Economic Performance with Environmental Disclosure as an intervening variable. The exploration subjects are manufacturing companies listed on the Indonesia Stock Exchange for the 2019-2020 period. This study uses a descriptive and verification approach. The data analysis technique in this research is descriptive analysis and path analysis. Based on the sampling criteria, there were 88 samples as data sources. The results of the analysis show that in the era of the covid-19 pandemic, Environmental Performance does not affect Environmental Disclosure, nor does it affect Economic Performance either directly or through Environmental Disclosure. In general, the Environmental Performance is quite good, but it is not able to improve the company's profitability. This is due to the massive impact of the pandemic, causing the weakening of the national economic growth rate, thus having an impact on the manufacturing industry in Indonesia.